2020
DOI: 10.1111/cei.13543
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin-18 in the diagnosis and monitoring of hemophagocytic lymphohistiocytosis/macrophage activation syndrome – a systematic review

Abstract: Summary Hemophagocytic lymphohistiocytosis (HLH) is a life-threatening, hyperinflammatory disorder, characterized by multiorgan failure, fever and cytopenias. The diagnosis of HLH and its subtype Macrophage Activation Syndrome (MAS) remains a challenge. Interleukin 18 (IL-18) is emerging as a potential biomarker for HLH/MAS but is currently not a part of diagnostic criteria. This systematic review aimed to assess the potential role of IL-18 in the diagnosis and monitoring of HLH and MAS, and was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…To the best of our knowledge, no comparative study of AOSD, HLH, and MAS has been ever performed in adults, whereas there are numerous studies comparing sJIA, HLH, and MAS in pediatric populations. Krei et al recently conducted a systematic review of 14 studies regarding the potential role of IL-18 in the diagnosis of HLH or MAS mainly in children (17). In that review, the serum IL-18 levels of the patients with active sJIA were approx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge, no comparative study of AOSD, HLH, and MAS has been ever performed in adults, whereas there are numerous studies comparing sJIA, HLH, and MAS in pediatric populations. Krei et al recently conducted a systematic review of 14 studies regarding the potential role of IL-18 in the diagnosis of HLH or MAS mainly in children (17). In that review, the serum IL-18 levels of the patients with active sJIA were approx.…”
Section: Discussionmentioning
confidence: 99%
“…Macrophage activation syndrome (MAS), an acquired form of HLH that occurs in autoimmune diseases, is a common and serious complication of AOSD, and it is especially difficult to distinguish AOSD-related MAS from HLH or MAS with other underlying diseases (16). It was recently revealed that serum IL-18 levels are increased in primary (genetic) and secondary HLH, especially in pediatric patients, and several reports have compared the serum IL-18 levels between pediatric HLH cases and patients with systemic juvenile idiopathic arthritis (sJIA), a homolog of AOSD in children (17). There have been few similar comparative studies between AOSD and adult HLH.…”
Section: Introductionmentioning
confidence: 99%
“…Our retrospective findings need to be confirmed by further studies, as the number of HLH diagnoses could have been underestimated (potentially incomplete medical coding) or overestimated (low specificity of HLH-2004 and HScore criteria). Besides, the advent of the cytokine era supporting HLH diagnosis (27)(28)(29) was not available in most patients of our cohort due to both retrospective design, time of inclusion and parameters unscreened routinely. In addition, retrospective etiological diagnosis can be difficult, as various concomitant etiologies can lead to HLH.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, anakinra (IL1Ra), rilonacept (IL1 inhibitor) and canakinumab (anti-IL1β) have been successfully studied in clinical research with comparable long-term efficacy where half of treated patients achieved remission [ 61 , 64 – 67 ]. IL18 may be another target for treatment of sJIA resistant to IL1 and IL6 inhibition, as far as higher levels of IL18 have been associated with high ferritin levels reported in MAS [ 68 , 69 ].…”
Section: Treatmentmentioning
confidence: 99%